2022
DOI: 10.3390/ijms23031862
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Stimulants Limit Caffeine Transport at the Blood–Cerebrospinal Fluid Barrier

Abstract: Caffeine, a common ingredient in energy drinks, crosses the blood–brain barrier easily, but the kinetics of caffeine across the blood–cerebrospinal fluid barrier (BCSFB) has not been investigated. Therefore, 127 autopsy cases (Group A, 30 patients, stimulant-detected group; and Group B, 97 patients, no stimulant detected group) were examined. In addition, a BCSFB model was constructed using human vascular endothelial cells and human choroid plexus epithelial cells separated by a filter, and the kinetics of caf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Our model showed that CAF and CBZ have high permeabilities, and LP and CET showed low permeability. These results are consistent with previous studies using animal or cell-culture models [25,27,37,38]. CAF is a well-known positive control for simple diffusion across the BBB, and it showed high permeability in both blood and brain channels in our model.…”
Section: Discussionsupporting
confidence: 93%
“…Our model showed that CAF and CBZ have high permeabilities, and LP and CET showed low permeability. These results are consistent with previous studies using animal or cell-culture models [25,27,37,38]. CAF is a well-known positive control for simple diffusion across the BBB, and it showed high permeability in both blood and brain channels in our model.…”
Section: Discussionsupporting
confidence: 93%
“…When crossing the BBB, certain bio-chemical properties are favourable: lipophilicity (fat-solubility), small physical size, a molecular weight below 450 g/mol, and low hydrogen-bonding potential (meaning the molecule exists at a neutral charge at a physiological pH of 7.5). Caffeine falls into the small molecule category, with a molecular weight of 194 g/mol, and demonstrates amphipathicity, allowing it to cross the BBB using passive transport (Figure 1) [14,15].…”
Section: Mechanism Of Caffeine Transport Across the Bbbmentioning
confidence: 99%
“…Caffeine (1,3,7-trimethylxanthine, CAF), a plant alkaloid structurally related to adenosine, exerts numerous physiological and pharmacological effects on many organs, including the cardiovascular, renal, respiratory, and central nervous systems (Persad, 2011). Caffeine readily crosses the bloodbrain barrier located in cerebral microvascular endothelial cells and the blood-cerebrospinal fluid barrier located in the epithelial cells of the choroid plexus (ChP) (McCall et al, 1982;Ikeda-Murakami et al, 2022). In the brain, caffeine exerts most of its biological effects by antagonising adenosine receptors (ADORs) and, like adenosine, affects neurons and glial cells of all brain areas (Ribeiro and Sebastião, 2010).…”
Section: Introductionmentioning
confidence: 99%